Propagule pressure helps overcome adverse environmental conditions during population establishment - D.L. Saccaggi; J.R.U. Wilson; J.S. Terblanche (Current Research in Insect Science, 2021)
The establishment success of a population is a function of abiotic and biotic factors and introduction dynamics. Understanding how these factors interact has direct consequences for understanding and managing biological invasions and for applied ecology more generally. Here we use a mesocosm approach to explore how the size of founding populations and the number of introduction events interact with environmental conditions (temperature) to determine the establishment success of laboratory-reared Drosophila melanogaster. We found that temperature played the biggest role in establishment success, eclipsing the role of the other experimental factors when viewed overall. Under optimal temperature conditions propagule pressure was of negligible importance to establishment success.  At adverse temperatures, however, establishment success increased with the total founding population size. This effect was considerably stronger at the cold than at the hot extreme. Whether the population was introduced all at once or by increments (changing the number of introduction events) had a negligible global effect. However, once again, a stronger effect of increasing number of introduction events was seen at adverse temperatures, with hot and cold extremes revealing opposite effects: adding flies incrementally decreased their establishment success at the hot extreme, but increased it at the cold extreme. These differing effects at hot and cold thermal extremes implies that different establishment mechanisms are at play at either extreme. These results suggest that the effort required to prevent (or conversely, to facilitate) the establishment of populations varies with the environment in ways that can be complicated but predictable.